2021
DOI: 10.1111/jocn.15622
|View full text |Cite
|
Sign up to set email alerts
|

A challenging balancing act to engage children and their families in a healthy lifestyle – Nurses' experiences of child‐centred health dialogue in child health services in Sweden

Abstract: Aims and objectives To describe nurses' experiences of a child‐centred family guided intervention of obesity tested within the child health services targeting children identified with overweight and their caregivers. Background Interventions aiming to support families towards a healthier lifestyle can lead to decreased risk of overweight evolving into obesity in a child. At the same time, nurses have found dialogues on weight challenging and may therefore avoid them. Design Qualitative descriptive inductive de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Another explanation might be that caregivers experienced an emotional response when the BMI growth chart was used to identify overweight and did not accept additional care 13,37,42 . Several studies showed that health professionals felt uncomfortable introducing the topic of overweight and found health dialogues with families about overweight challenging 23,37,39 . Likewise, in our study nurses in both groups answered that they felt uncomfortable communicating about overweight.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Another explanation might be that caregivers experienced an emotional response when the BMI growth chart was used to identify overweight and did not accept additional care 13,37,42 . Several studies showed that health professionals felt uncomfortable introducing the topic of overweight and found health dialogues with families about overweight challenging 23,37,39 . Likewise, in our study nurses in both groups answered that they felt uncomfortable communicating about overweight.…”
Section: Discussionmentioning
confidence: 64%
“…In our study, a larger proportion of nurses in the intervention group believed they had adequate knowledge of child overweight and felt competent in the communication method. A qualitative study describing nurses' experiences of CCHD showed that CCHD encouraged nurses to mention their concern about the child's health in relation to their weight, which is an important step in the prevention of child obesity 36,37,39 . Nurses trained in CCHD felt that they had been provided with a toolbox that facilitated a more professional way of performing a dialogue with caregivers and children with overweight 39 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations